The Effect of Vermicompost and NPK Fertilizer on Growth of Long Beans (Vigna sinensis L.) - Ahmad Raksun; I Wayan Merta; Moh. Liwa Ilhamdi; Gde Mertha (Postgraduate, University of Mataram, 2022)
Long beans are short-lived plants that are widely cultivated in Indonesia. To stimulate the growth of long beans, it is necessary to fertilize with the appropriate dose for its growth. Research on the effect of vermicompost and NPK fertilizer has been carried out in Mertak Umbak Village, Central Lombok. The purpose of the research was to determine the effect of the application of vermicompost on the growth of long beans, the effect of the application of NPK fertilizer on the growth of long beans and the interaction effect of the application of vermicompost and NPK fertilizer on the growth of long beans. The research was carried out with a 2-factor design and 4 replications. The research data were analyzed by analysis of variance. In this study, the results showed that the treatment of vermicompost significantly increased the number of leaves and plant height, but could not increase the length and width of the long bean leaves, the application of NPK fertilizer could increase the leaf length, leaf width, number of leaves and stem length of long beans and the interaction of vermicompost and NPK fertilizer treatment did not significantly affect all measured long bean growth parameters